Plasma H2S predicts coronary artery lesions in children with Kawasaki disease. Issue 5 (29th May 2015) - Sun, Yan; Yuan, Yue; Yan, Hui; Wan, Hong; Li, Xueying; Chen, Siyao; Li, Hongxia; Tang, Chaoshu; Du, Junbao; Liu, Guiying; Jin, Hongfang
Abstract: Background: The aim of this study was to determine whether plasma hydrogen sulfide (H2 S) is a biomarker for predicting coronary artery lesions (CAL) in children with Kawasaki disease (KD). Methods: A prospective study was conducted on 50 KD patients and 27 healthy children. Plasma H2 S was analyzed at the acute stage. Plasma H2 S was detected using the sensitive electrode method, and receiver operating characteristic curve (ROC) analysis was carried out. Results: Plasma H2 S in KD patients at the acute stage was significantly lower than that of controls. CAL patients had reduced plasma H2 S at acute stage compared with the non‐CAL patients. A plasma H2 S cut‐off of 31.2 µmol/L provided a sensitivity of 81% and a specificity of 62.5% for predicting coronary injuries in KD. Optimal specificity and sensitivity were obtained when using plasma H2 S to predict CAL in KD children. Conclusion: Plasma H2 S level in the acute period is a potentially useful biomarker for predicting CAL in KD children.